Interspecific association of herbaceous plant communities on different slope orientations and at different altitudes in central Yunnan grasslands - Gong, Rui; Gong, He-de (Frontiers in Plant Science, 2024)
Aims Understanding the response of herbaceous plants to habitat changes and the mechanisms of vegetation succession is crucial to the theoretical foundation of the conservation of local vegetation. Methods Plots were established at elevations of 1900-2200m, 2200-2500m, and 2500-2800m on both shady and sunny slopes. Four statistical methods 2×2 contingency table χ2-test, Spearman's rank correlation coefficient, AC joint coefficient, 17 and Ochiai Index, were employed to analyze the species composition and interspecific associations within each elevation band and aspect. Important findings (1) the number of herbaceous plant species was greater on the sunny slope than on the shady slope; the number of species was higher in the2 elevation bands of 1900-2200m and 2200-2500m than in 2500-2800m. (2) Both AC joint coefficient and Ochiai Index revealed that the interspecific connectivity increased as elevation increased on the shady slope, although the highest interspecific connectivity was observed in the 2200-2500m elevation rather than other two elevations on the sunny slope. (3) Negative associations among species pairs were more prevalent than positive associations on both the shady and sunny slopes at all elevations,indicating a high level of negative interspecific associations and connectivity. (4) χ2-test values and Spearman rank correlation analysis indicated that it was a relatively unstable community.However, an overall more stable community on the shady slope.The influence of altitude and slope orientation on interspecific associations has wide applications in multiple fields. By deeply understanding the role of these environmental factors, scientists, agricultural workers, forestry managers, and protectors can better carry out work in resource management, species conservation, climate change adaptation, and other aspects.